A replacement name for the Cretaceous termite genus Gigantotermes (Isoptera) - Engel, Michael S.; Barden, Phillip M.; Grimaldi, David A. (Novitates Paleoentomologicae, 2016)
A replacement name is proposed in order to remove a case of secondary homonymy between the Cretaceous termite genus Gigantotermes Engel, Barden, & Grimaldi (Isoptera) and the Jurassic lacewing, Gigantotermes Haase (Neuroptera). Ginormotermes Engel, Barden, & Grimaldi, new name, is established in place of the former, resulting in the new combination: Ginormotermesrex (Engel, Barden, & Grimaldi).